2011
DOI: 10.18632/oncotarget.346
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of PIK3CA or PIK3R1 reduces proliferation, migration, and invasion in glioblastoma multiforme cells

Abstract: Glioblastoma multiforme (GBM) is a highly invasive and deadly brain tumor. Tumor cell invasion makes complete surgical resection impossible and reduces the efficacy of other therapies. Genome-wide analyses of mutations, copy-number changes, and expression patterns have provided new insights into genetic abnormalities common in GBM. We analyzed published data and identified the invasion and motility pathways most frequently altered in GBM. These were most notably the focal adhesion and integrin signaling, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 58 publications
5
71
0
2
Order By: Relevance
“…These include the previous observation that PRMT1 triggers methylation-mediated association of ERα with PI3-kinase, Src and FAK complex, 19 all of which regulate cell migration and invasion. [69][70][71][72][73] Furthermore, it has been shown that mutation of p53 is involved in the regulation of cell migration and invasion, increasing the metastatic potential of cancer cells. 74,75 While PRMT1 was previously shown to participate in p53-dependent transcriptional activation, 47 it remains unknown whether this may be linked with the mechanisms through which PRMT1v2 promotes breast cancer cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…These include the previous observation that PRMT1 triggers methylation-mediated association of ERα with PI3-kinase, Src and FAK complex, 19 all of which regulate cell migration and invasion. [69][70][71][72][73] Furthermore, it has been shown that mutation of p53 is involved in the regulation of cell migration and invasion, increasing the metastatic potential of cancer cells. 74,75 While PRMT1 was previously shown to participate in p53-dependent transcriptional activation, 47 it remains unknown whether this may be linked with the mechanisms through which PRMT1v2 promotes breast cancer cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…39 The abrogation of PIK3CA or PIK3R1 also reduces proliferation, migration and invasion, since these two genes are frequently found to be mutated and overexpressed in GBM. 40 NFκB is also viewed as an important therapeutic target of GBM, which implicates IKKβ inhibitors in interfering with NFκB activation in order to prohibit the limitless replicative potential, tissue invasion interrelationships among GSK3b, BCL2L12 and BCL2L12A in glioblastoma, as shown in Figure 6. Our present results indicate that overexpression of BCL2L12 and BCL2L12A in U87MG leads to STS resistance.…”
Section: Discussionmentioning
confidence: 99%
“…One plausible underlying mechanism could be decrease in the amount of p110-unbound p85α, which is tumor suppressive as described earlier. However, it is important to note that in vitro knockdown of PIK3R1 resulted in decreased proliferation, migration and invasion in glioblastoma multiforme cells [87], suggesting that increased or decreased p85α levels could have similar effects on tumor progression depending on the context.…”
Section: Future Science Groupmentioning
confidence: 99%